Monitoring and Evaluation Model Construction for Enhancing the Effectiveness of Productive Zakat Management in BAZNAS Malang Regency - Minarni, Minarni; Dwi Ayuningtyas, Rosida; Qurroti Aeni, Reni; Imron, Moh.; Susanto, Dwi Yulis (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2026)
Productive zakat is a strategic Islamic philanthropic instrument in overcoming poverty and encouraging the improvement of the welfare of mustahiq (recipients of zakat). Badan Amil Zakat Nasional (BAZNAS) of Malang Regency has implemented monitoring and welfare improvement programs for productive zakat to encourage community economic independence. However, its effectiveness has not been optimal, especially since performance indicators are not yet integrated, sustainable, and based on Islamic spiritual values. BAZNAS Malang Regency still faces limitations in sustainable mentoring and long-term impact measurement. This study aims to describe and analyze the implementation of monitoring and evaluation of productive zakat programs, as well as construct an effective model to improve program performance and impact. The study used a qualitative approach with a case study design. Informants included BAZNAS administrators, mustahiq, and stakeholders, who were selected purposively. Data were collected through interviews, observation, and documentation, then analyzed using content analysis with triangulation of sources and methods. The results indicate that monitoring and evaluation have been carried out in a structured manner, but limited sustainable mentoring and variations in business capacity remain obstacles. Therefore, strengthening the monitoring and evaluation system, business mentoring, reporting documentation, and stakeholder collaboration are needed to improve the effectiveness of productive zakat management. The novelty of this research is a continuous improvement-based model that integrates results-based monitoring and evaluation with the values ​​of amanah, ihsan, and hisbah to increase the effectiveness of productive zakat management